5x-3(x-5)=-8+5x+14

Simple and best practice solution for 5x-3(x-5)=-8+5x+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3(x-5)=-8+5x+14 equation:


Simplifying
5x + -3(x + -5) = -8 + 5x + 14

Reorder the terms:
5x + -3(-5 + x) = -8 + 5x + 14
5x + (-5 * -3 + x * -3) = -8 + 5x + 14
5x + (15 + -3x) = -8 + 5x + 14

Reorder the terms:
15 + 5x + -3x = -8 + 5x + 14

Combine like terms: 5x + -3x = 2x
15 + 2x = -8 + 5x + 14

Reorder the terms:
15 + 2x = -8 + 14 + 5x

Combine like terms: -8 + 14 = 6
15 + 2x = 6 + 5x

Solving
15 + 2x = 6 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
15 + 2x + -5x = 6 + 5x + -5x

Combine like terms: 2x + -5x = -3x
15 + -3x = 6 + 5x + -5x

Combine like terms: 5x + -5x = 0
15 + -3x = 6 + 0
15 + -3x = 6

Add '-15' to each side of the equation.
15 + -15 + -3x = 6 + -15

Combine like terms: 15 + -15 = 0
0 + -3x = 6 + -15
-3x = 6 + -15

Combine like terms: 6 + -15 = -9
-3x = -9

Divide each side by '-3'.
x = 3

Simplifying
x = 3

See similar equations:

| 53=a^3+b^3+c^3 | | 9x-7i=3(3i-7u) | | 54=a^3+b^3+c^3 | | 29=a^3+b^3+c^3 | | x^3+6x^2-5x-22=0 | | a(a+b)-b(a+b)= | | y=0.7x+0.6 | | 2a^2-a+4=14a-14 | | 7.5n-1.5=-6.5+6.5n | | 3(b+2)-(b-4)=0 | | 9+x=3x+3 | | x^4-x^3-11x^2+29x+78=0 | | 3a+4=14a-14 | | (1-x)+5c(1-x)= | | x^2(p+q)+y^2(p+q)= | | 5n+7(-6+n)=4(n+3) | | (3a+4)*(a-1)=14 | | 6x+9y+3x+4x= | | x+19+x=79 | | 3.5x+1.2y=8 | | 5x+6x-57=38-8x | | .25*x=57 | | 4+2x=8+2x | | 3.5x+1.2y= | | F(x)=3-x/2 | | 3(x-6)=4(x+4) | | 152+.3x=2.2x | | a(x+1)+b(x+1)= | | 3=4-1 | | .25x*x=57 | | a(x+1)+b(x+1)= | | 4+2x=8x+2x |

Equations solver categories